Communication ethics and abuse in Facebook-based da'wah among Yoruba Muslims - Daud Olalekan Abdulsalam; Abdulrasheed Mubashir Abubakar; Abdulhameed Uthman (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2026)
The emergence of social media has transformed Islamic communication by enabling Muslim scholars and daʿwah practitioners to disseminate religious teachings beyond geographical boundaries. Among these platforms, Facebook has become a prominent medium for daʿwah among Yoruba Muslims in southwestern Nigeria. While previous studies have emphasized the opportunities offered by digital daʿwah, limited attention has been paid to the abuse of Facebook-based daʿwah and its implications for Muslim communities. This study investigates the abuse of daʿwah activities on Facebook and their effects among Yoruba Muslims. A qualitative descriptive research design was adopted, using non-participant observation and thematic content analysis. Data were collected from three purposively selected Facebook pages: Star Lady Entertainment, Save Your Soul TV, and Yesaloonaka through observations of live sermons, counselling sessions, audience comments, debates, and other online interactions, complemented by relevant scholarly literature. The findings reveal that although Facebook has expanded the reach of Islamic propagation, abusive practices such as offensive language, sectarian polarization, misinformation, emotional manipulation, cyberbullying, commercialization of daʿwah, and public humiliation increasingly undermine Islamic communication ethics and contribute to social tension and weakened respect for religious authority. The study concludes that effective digital daʿwah requires adherence to Islamic ethical principles and recommends ethical guidelines, stronger moderation, digital literacy, and greater accountability among daʿwah practitioners. It contributes empirical evidence to the growing scholarship on digital religion within the Yoruba Muslim context. ***** Kemunculan media sosial telah mentransformasi komunikasi Islam dengan memungkinkan para ulama Muslim dan praktisi dakwah menyebarluaskan ajaran Islam melampaui batas-batas geografis. Di antara berbagai platform tersebut, Facebook telah menjadi media yang menonjol untuk dakwah di kalangan Muslim Yoruba di Nigeria bagian barat daya. Meskipun penelitian-penelitian sebelumnya telah menekankan berbagai peluang yang ditawarkan oleh dakwah digital, perhatian terhadap penyalahgunaan dakwah berbasis Facebook serta implikasinya bagi komunitas Muslim masih terbatas. Penelitian ini menyelidiki penyalahgunaan aktivitas dakwah di Facebook beserta dampaknya di kalangan Muslim Yoruba. Penelitian ini menggunakan desain penelitian deskriptif kualitatif dengan menerapkan observasi nonpartisipan dan analisis isi tematik. Data dikumpulkan dari tiga halaman Facebook yang dipilih secara purposif, yaitu Star Lady Entertainment, Save Your Soul TV, dan Yesaloonaka, melalui observasi terhadap ceramah langsung, sesi konseling, komentar audiens, perdebatan, serta berbagai interaksi daring lainnya, yang dilengkapi dengan literatur ilmiah yang relevan. Hasil penelitian menunjukkan bahwa meskipun Facebook telah memperluas jangkauan penyebaran dakwah Islam, berbagai praktik penyalahgunaan seperti penggunaan bahasa yang ofensif, polarisasi sektarian, misinformasi, manipulasi emosional, perundungan siber, komersialisasi dakwah, dan penghinaan di ruang publik semakin mengikis etika komunikasi Islam serta berkontribusi terhadap meningkatnya ketegangan sosial dan melemahnya penghormatan terhadap otoritas keagamaan. Penelitian ini menyimpulkan bahwa dakwah digital yang efektif memerlukan kepatuhan terhadap prinsip-prinsip etika Islam, serta merekomendasikan penyusunan pedoman etika, penguatan moderasi, peningkatan literasi digital, dan akuntabilitas yang lebih besar di kalangan praktisi dakwah. Penelitian ini memberikan bukti empiris yang memperkaya khazanah kajian tentang agama digital dalam konteks komunitas Muslim Yoruba.